Perancangan perhiasan transformable berbasis budaya Wae Rebo untuk perempuan paruh baya - Wyna Herdiana; Zahwa Aulia Mashur (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
Jewelry is not only an aesthetic element, but also a cultural artifact that reflects a community’s values, identity, and way of life. This study aims to develop a transformable jewelry concept based on Wae Rebo cultural values while considering the needs of middle-aged women as the main users. Women aged 46–55 were selected because they tend to prioritize comfort, ease of use, and product flexibility in their daily activities. This study uses a qualitative approach with a research-based design method through literature review, observation, visual analysis, and interviews. The data were analyzed using the ATUMICS framework to systematically translate Wae Rebo cultural values into the design concept. The study resulted in a set of transformable jewelry consisting of a necklace, bracelet, earrings, and brooch with a modular system that allows changes in appearance and function according to the user’s needs. Wae Rebo cultural values were interpreted through form, layered structure, interconnected elements, and the ideas of harmony and togetherness without reproducing cultural symbols literally. The resulting design emphasizes ergonomics, ease of use, and flexibility, making it relevant for middle-aged women while still preserving cultural meaning as its source of inspiration. Published Date: 2026-07-30